ASEAN-India: strengthening people-to-people ties - Tan, Ming Hui (World Scientific Publishing, 2024)
The year 2022 marks the 30th anniversary of the dialogue relations between the Association of Southeast Asian Nations (ASEAN) and India and has been designated the ‘ASEAN-India Friendship Year’. On top of a long history of cross-civilisational linkages and people-to-people exchanges, ASEAN-India modern-day relations have seen positive and steady improvements since the end of the Cold War…